EUTHANASIA, AUTONOMY AND THE FREE DISPOSING OF ONE´S OWN LIFE - Pérez Sánchez, Elías (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
Traditional arguments against disposing of one´s own life are still valid in part: in some societies attempting suicide is still considered a crime, and collaboration with-or complicity- is likewise criminal behavior. Nevertheless, in the last few years there has come about a growing recognition of “the right to a dignified death”. Al the same, that right comes with certain conditions which, to my way of thinking turn it more into a catchy, deceptive slogan rather than into a clearly consolidated and recognized right. The present article will attempt to explain the different arguments for and against the free disposing of one´s own life as put forward throughout the history of western thinking. Afterwards an attempt will be made to show that the free disposal of one´s own life meets with too many restrictions in Spain, and that in some of them there are underlying extra secular principles, unbecoming to a democratic, multicultural and secular society such as ours.